Functions of mucosal associated invariant T cells in eye diseases - Fukui, Chihiro; Yamana, Satoshi; Xue, Yanqi; Shirane, Mariko; Tsutsui, Hiroki; Asahara, Kenichiro; Yoshitomi, Keiko; Ito, Takako; Lestari, Tantri; Hasegawa, Eiichi; Yawata, Nobuyo; Takeda, Atsunobu; et al. (Frontiers in Immunology, 2024)
Mucosal-associated invariant T (MAIT) cells are a unique subset of T cells that recognizes metabolites derived from the vitamin B2 biosynthetic pathway. Since the identification of cognate antigens for MAIT cells, knowledge of the functions of MAIT cells in cancer, autoimmunity, and infectious diseases has been rapidly expanding. Recently, MAIT cells have been found to contribute to visual protection against autoimmunity in the eye. The protective functions of MAIT cells are induced by T-cell receptor (TCR)-mediated activation. However, the underlying mechanisms remain unclear. Thus, this mini-review aims to discuss our findings and the complexity of MAIT cellmediated immune regulation in the eye.